A imagem do destino turístico, na percepção dos atores do trade turístico: um estudo da cidade histórica de Diamantina/MG - Danielle Fernandes Costa Machado (2010)
The aim of this study was to analyze the image of the destination, according to the perception of the host community, tourists and the public managers which compose the tourist trade. The study proposal was based on the General Model of Images in Travel, formulated bySantana (2009) and on previous studies which recognize the pluralistic and relativistic nature of the places image. The historic city from Minas Gerais state, Diamantina, was chosen as the place of research because of the increasing importance governmental programs are giving to thedestination as a pole which attracts national and international tourism. The research operational procedures involved several methods to collect data such as photoetnography, documental research, semi-structured surveys and projection techniques, choosing, therefore, a qualitativeapproach, deemed as more appropriate to the purposes of this study. Data analysis was done based on the technique of content analysis, which resulted in the recognition of five categories related to Diamantinas image, in agreement with the already established theories in the area: 1) the symbolic meanings attributed to tourism involving the different social actors, 2) the dimension of the holistic image of the destination, referring to the similarities and differences between the perceptions of different research groups and individuals; 3) the evaluation of theattributes of the image of Diamantina by local actors, 4) the tourism promotion held by public managers; 5) the perception of the brand personality of the destination and its psychological dimension to intervene in market positioning. The conclusion indicates that perceptions of the actors on the tourist destination can help to identify the characteristics of the authenticity of the place and the most valued attributes by tourists from its experience with the travel destination.The results also reveal that, in general, there is agreement as to the various dimensions of the perceived image of Diamantina among local actors. However, the image induced by municipal managers is misguided in a strategic point of view, because in addition of being weak and inconsistent, can not pass consistently the attributes of the image of the place which were identified as enhancers of the competitive differential mark of the destination. In contrast, the tourism promotion that so far has been developed serves more intensively to reinforce thestereotype of "historic town from Minas Gerais" than to add value to the places brand.